New Product Launch and Stock Returns in the Period of Demonetization : Cross Section and Multivariate Time Series Analysis - Joshi, Himanshu (Indian Journal of Research in Capital Markets, 2017)
The period of demonetization witnessed negative stock returns and earnings growth rates across various industries in India. The average weekly returns during this period on benchmark BSE Sensex was -0.42%, translating into an annualized return of -20.34 %. Using the discounted cash flow (DCF) valuation formula, under the imperfect market conditions, new product innovations can create shareholders' value by affecting one of the two variables: (a) future cash flows that are expected to be produced by the business ; and (b) capital providers' required rate of return at which those cash flows are discounted by the market. A firm can beat competition and increase its future cash flows by indulging in product innovation and launching such new products, which are able to command higher prices in the consumer market. New product innovations can also support the revival of products, which are in declining stages of their product lifecycle, and in turn can reduce uncertainty around a firm's cash flows. Reduction in cash flow uncertainty results in lower required rate of returns by capital providers. Consequently, new product launches can create shareholders' value, which can be captured by stock returns. The present paper used cross section data for listed Indian firms to study investors' response to new product launches in the period of demonetization, that is, October - December 2016. To establish a long-term effect of new product launches on stock returns, a multivariate time series analysis was also conducted for a single firm Maruti Suzuki for 26 quarters ending December 2016. The results suggested that a new product launch has a significant positive impact on quarterly EPS growth rate, and stock returns in the long run as well as in the short run. Also, in the crisis period of demonetization, where all the firms across various industries registered negative growth in EPS and hugely negative stock returns, new product launch worked as a savior for the firm.